Forensic Geotechnical Engineering - Rao, V.V.S.; Sivakumar Babu, G.L.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
In this edited volume on advances in forensic geotechnical engineering, a number of technical contributions by experts and professionals in this area are included. The work is the outcome of deliberations at various conferences in the area conducted by Prof. G.L. Sivakumar Babu and Dr. V.V.S. Rao as secretary and Chairman of Technical Committee on Forensic Geotechnical Engineering of International Society for Soil Mechanics and Foundation Engineering (ISSMGE). This volume contains papers on topics such as guidelines, evidence/data collection, distress characterization, use of diagnostic tests (laboratory and field tests), back analysis, failure hypothesis formulation, role of instrumentation and sensor-based technologies, risk analysis, technical shortcomings. This volume will prove useful to researchers and practitioners alike. .
A Framework for Forensic Foundation Engineering -- Forensic Geotechnical Engineering Theory and Practice -- Guidelines for Forensic Investigation of Geotechnical Failures -- Caisson Failure Induced by Wave Action -- Forensic Geotechnical Engineering Investigations: Data Collection -- Diagnosis of Geotechnical Failure Causes Using Bayesian Networks -- Back Analyses in Geotechnical Engineering -- Back Analysis of Slope Failures to Design Landslide Stabilizing Piles -- Back Analyses in Forensic Geotechnical Engineering -- Instrumentation and Monitoring for Forensic Geotechnical Engineering -- Analysis of the Causes of Undue Movements of a Retaining Wall used to form a Deep Basement in Sandstone and Consequent Damage to an Adjacent Canal -- Failure Mechanism of Anchored Retaining Wall Due to the Breakage of Anchor Head -- Backwards Problem in Geotechnical Earthquake Engineering -- Failure Analysis of Underground Construction - Lessons Learned from Taiwan -- Failure Analysis of a Highway Dip Slope Slide -- Characterization of Failure at a Large Landslide in Se Queensland by Geological Mapping, Laboratory Testing, Instrumentation and Monitoring -- Post-liquefaction Data Collection and Analyses for Earthquakes in New Zealand -- Forensic Geotechnics - Some Case Studies from Singapore -- Technical Shortcomings Causing Geotechnical Failures: Report of Task Force 10, TC 302 -- Effects of Vibration by Demolition to nearby Machine Shop Floor - Wave Measurement for Dynamic Property of Ground -- A Case of Piping in Sand under a Dam and its Back Analysis -- Influence of Vibrations on Installation of Bored Piles -- Aspects regarding Management of Soil Risk -- Forensic Studies for Failure in Construction of an Underground Station of the Kaohsiung MRT System -- Damage to a Metro Tunnel Due to Adjacent Excavation -- A Case Study of Floor Heaving of a Condominium RC-Building with Seven Stories -- Failure Case Study of Tieback Wall in Urban Area, Korea -- Forensics of Pile Foundations Subjected to Earthquake Induced Liquefaction and Lateral Spreading -- Piping Failure of a Metro Tunnel Construction -- Forensic Analysis of Failure of Retaining Wall -- Role of Reliability in Forensic Geotechnical Engineering -- Important Role of Uncertainty in Forensic Geotechnical Engineering -- Technical, Ethical, and Legal Issues with Forensic Geotechnical Engineering - A Case History -- Forensic Engineering, Legal Considerations, and Property Damage Assessment from Construction Vibrations -- A Case Study of Observational Method for a Failed Geotechnical Excavation in Singapore. .
Keywords: Engineering geology; Geotechnical engineering; Natural disasters; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Natural Hazards